FORMULATION AND DEVELOPMENT OF TOPICAL ANTI ACNE FORMULATION OF SPIRULINA EXTRACT - Nihal, Badduri; Gupta, N. Vishal; Gowda, D. V.; M., Manohar (International Journal of Applied Pharmaceutics, 2018)
Objective: The objective of this research was to formulate and evaluate anti-acne ointment of C-phycocyanin(C-PC) extracted from spirulina. Methods: C-PC was successfully extracted from spirulina by using sonication and cold-maceration process and further purified by dialysis method. By employing disc diffusion and agar dilution method, antimicrobial activity and minimum inhibitory concentration(MIC) of C-PC as determined against Propionibacterium acne (P. acne) and Staphylococcus epidermidis(S. epidermidis). Further, the two different formulations were prepared by using water soluble and oleaginous bases, and the formulations were characterized for particle size, viscosity, pH, consistency, drug diffusion, antimicrobial activity, and antioxidant effect and stability studies. Results: C-PC showed MIC value of 1.5±0.1 mg/ml and 1.8±0.2 mg/ml against P. acne and S. epidermidis respectively. The developed formulation had a globule diameter of 5.44 mm, pH of 6.8±0.09, the viscosity of 175±0.2cps, spreadability of an 8.6±0.12g. cm/sec and had good consistency. Both formulations were found stable among which, formulation B(FB) had maximum drug content of 95±0.6% and drug release was up to 92±0.8%. Conclusion: The prepared topical C-PC ointment can be successfully employed in the treatment of acneagainstP. acne and S. epidermidis.